Pengembangan dan efektivitas model konseling behavioristik teknik role playing serta modeling untuk meminimalisir perilaku bullying siswa - Ni Nyoman Diastrimarina; I Ketut Dharsana; Kadek Suranata (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
The aims of this study is to (1) compile and produce a behavioristic counseling guidebook, (2) determine the content's validity of the behavioristic counseling guidebook, (3) find out the practicality of a behavioristic counseling guidebook, and (4) determine the effectiveness of a behavioristic counseling guidebook using the role playing technique. as well as modeling to minimize bullying behavior of junior high school students. This research method uses research and development (R&D) with the 4D (Four D) model developed by Thiagarajan (1974). This study used a bullying behavior questionnaire as an instrument. Expert examiner on the guide product involve five experts from Guidance and Counseling Professors. The results of this study indicate that (1) produce a behavioristic counseling guidebook consisting of covers, prefaces, guide schemes, steps, evaluation and closing (2) behavioristic counseling guidebooks using role playing techniques and modeling to minimize student bullying behavior are declared valid. high with CVR = 1 (CVR> 0) and CVI got a score of 1, (3) the practicality test of the guidebook on the assessment of five guidance counseling practitioners was declared practical (89%), (4) The application of the guidebook behavioristic counseling technique role playing and Effective modeling is used to minimize student bullying behavior with a value of t = 19.171 with a significance <0.05